Reflecting on a DBA Journey - Leonidou, Erasmia; Christofi, Michael (My University, 2012)
Each one experiences an incentive and a journey through the lenses of our paradigms with a unique way. Reflecting on those paradigms and the procedure of questioning the accuracy of those ‘mental maps’ during an advanced academic qualification, will contribute to the development of an academic identity. The ignorance of the existence of those ‘maps’ slows down the process of self-knowledge and self-development. Reflection on the things that generate dilemmas, conflicts, risks and uncertainty becomes fundamental during a DBA journey as it may eventually lead to an outcome. People would get the best out of a reflected action while writing a learning journal. Reflecting on the understanding and the representation of the understanding is very crucial in the development of critical thinking and general questioning.
Keywords: Learning Journals; Critical Reflection; Reflection; DBA; Learning; Problem Solving